Perspektif Generasi Z tentang Pelaksanaan Budaya Maano dalam Kesatuan Masyarakat Hukum Adat Negeri Piru - Agustinus Nindatu; Louisa M. Metekohy (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
The main objective of this study is to analyze the perspective of generation z on the implementation of maano culture in the unity of the Piru customary law community. Generation Z is a generation that interacts with technological advances. As a digital generation, technological advances should lead them to be more familiar with local cultures such as maano culture, as a local culture, generation Z must really have knowledge and constructive views on maano culture by grounding this culture to be known to the public as a local culture of the Piru customary law community in particular and the Maluku customary community in general. This qualitative research was conducted using the side snowball technique on generation Z of the Piru customary law community through interview and documentation techniques. then analyzed descriptively qualitatively. The target achievement of this study resulted in. The existence of Maano culture that for generation z of the Piru customary law community states that for some generations they know maano culture through the process of cultural inheritance and for some new generations they know through formal education. Therefore, maano culture is rarely found in Piru society. The existence that has been increasingly lost is caused by several things, namely the absence of a cultural inheritance process, the emergence of an individualistic attitude. In fact, maano culture can foster a sense of togetherness, mutual help and cooperation The efforts to preserve Maano culture that Maano culture should be introduced from generation to generation so that this culture continues to be known and developed by the next generation. Generation Z provides some hope that Maano culture should be introduced more deeply to other Generation Z, and as a digital generation, Maano culture is introduced through social media so as to spur a sense of love for local culture.